"On time ‐ every time" A new strategy for dosing levodopa in hospital. (2nd August 2020) - Ortiz, Michael S.
Abstract: Most Parkinson's Disease (PD) patients are hospitalised for reasons other than their PD. Their PD symptoms are usually under control before admission, however, too many seem to experience medication‐related problems in hospital. Hospitalised PD patients should receive their levodopa within 30 min of the scheduled time ("on time") and not miss doses ("every time"). Hospital staff should avoid prescribing and administering contraindicated dopamine antagonists to PD patients in their care. Multiple studies have shown the failure to deliver levodopa "on time" to PD patients, with less than 50% of doses being "on time" and an average 0.7 of doses missed each day. The evidence points to hospital medication administration systems (HMAS) as the likely cause of late and missed levodopa doses. PD medication administration guidelines were reviewed to find strategies that reduced late and missed doses. An integrated "on time – every time" medication administration approach is proposed. PD patients should be encouraged to self‐administer their medication in hospital. More PD nurse navigators will be needed to facilitate PD patient care in Australian hospitals.